2012
DOI: 10.1080/14616734.2012.636658
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and discontinuity of attachment patterns: A short-term longitudinal pilot study using a sample of late-adopted children and their adoptive mothers

Abstract: This study analysed the attachment patterns of 28 late-adopted children (placed when they were between four and seven years of age) and their adoptive mothers. The change in the children's internal working models (IWMs) within seven to eight months of their placement was evaluated. In addition, we wanted to observe the influence of a secure-autonomous maternal state of mind in facilitating the change in the children's IWMs and the possible associations between the maternal IWMs and the children's IWMs in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 42 publications
4
60
1
1
Order By: Relevance
“…The earned security (Pace et al, 2012) in the behavioural pattern of Kiwot was supported by the secure attachment representation revealed by the MCAST classified as secure with mild index of disorganization (Table 2). A secure classification is assigned when the strategy of attachment is characterized by the representation of an interaction of proximity with the caregiver that brings an assuagement of the discomfort.…”
Section: Manchester Child Attachment Story Taskmentioning
confidence: 69%
See 1 more Smart Citation
“…The earned security (Pace et al, 2012) in the behavioural pattern of Kiwot was supported by the secure attachment representation revealed by the MCAST classified as secure with mild index of disorganization (Table 2). A secure classification is assigned when the strategy of attachment is characterized by the representation of an interaction of proximity with the caregiver that brings an assuagement of the discomfort.…”
Section: Manchester Child Attachment Story Taskmentioning
confidence: 69%
“…Scores of 1-9 on 33 scales and a final classification -secure (B), avoidant (A), ambivalent (C), disorganized (D) -are then assigned to each story. From these codes, it is possible to add more scores from three global scales -coherence of mind, mentalization, and disorganization -and a final classification -A, B, C and D -to the whole MCAST (Pace, Zavattini & D'Alessio, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Kaniuk et al (2004) found that adoptive mothers with secure attachment styles had more successful adoptions 'Where these interventions have been trialled with foster or adoptive parents specifically, the results suggest limited value' 'Frequency of placement moves once within the child welfare system mean that this 'secure base' is unlikely to have been established' than those with insecure attachment styles, and Pace et al (2012) found that mothers who were classified as secure-autonomous were more likely to have securely attached adopted children six months post placement. In a fostered population, Dozier et al (2001) found that attachment styles were concordant between infants and their carers three months post placement, suggesting that insecurely attached infants may shift to a secure attachment pattern when placed with secure-autonomous adults.…”
Section: Caregiver Attachmentmentioning
confidence: 92%
“…Adoptive parents are faced with an even more challenging task than biological parents are: that of developing and consolidating an attachment bond with a child whose early development may have taken place in neglectful or abusive contexts, who is more at risk for behavioral and social-emotional problems (Barone, Dellagiulia, & Lionetti, in press;Muhamedrahimov et al, 2014;Pace, Zavattini, & D'Alessio, 2012), and whose reactions might not always be consistent with parental expectations (Dozier…”
Section: Introductionmentioning
confidence: 96%